2021
DOI: 10.1167/tvst.10.11.12
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Cytokine Levels Are Associated With Progression of Peripheral Anterior Synechiae After Descemet Stripping Automated Endothelial Keratoplasty

Abstract: Purpose To evaluate the association between total protein and cytokine levels in aqueous humor (AqH) and the progression of peripheral anterior synechiae (PAS) after Descemet stripping automated endothelial keratoplasty (DSAEK). Methods This prospective study included 146 consecutive patients who underwent DSAEK. Preoperative levels of total protein and 20 cytokines in AqH were measured. Using three-dimensional anterior segment optical coherence tomography, we assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…PAS did not progress in 12 eyes (13.8%) with preoperative PAS. To evaluate PAS severity, we measured the degree, height and area of irido-trabecular contact (ITC) using three-dimensional AS-OCT, as previously reported [24]. The ITC indices (ITC %degree, maximal height and area) gradually increased after PKP; however, all ITC indices significantly increased at 12 months after PKP, compared to the preoperative values (Table 1, p < 0.03).…”
Section: Pas After Pkpmentioning
confidence: 83%
See 4 more Smart Citations
“…PAS did not progress in 12 eyes (13.8%) with preoperative PAS. To evaluate PAS severity, we measured the degree, height and area of irido-trabecular contact (ITC) using three-dimensional AS-OCT, as previously reported [24]. The ITC indices (ITC %degree, maximal height and area) gradually increased after PKP; however, all ITC indices significantly increased at 12 months after PKP, compared to the preoperative values (Table 1, p < 0.03).…”
Section: Pas After Pkpmentioning
confidence: 83%
“…Recent advances in anterior segment optical coherence tomography (AS-OCT) have enabled the non-invasive and accurate quantification of PAS [13][14][15][19][20][21][22][23]. Using stateof-the-art AS-OCT, we have demonstrated that the elevated levels of specific cytokines in the aqueous humor (AqH) were significantly correlated with the development of PAS after EK [24]. This suggests that the inflammatory microenvironment in AqH leads to PAS development and refractory glaucoma after corneal transplantation.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations